State Administrative Law Reform in Realizing Good Governance and Legal Certainty in Indonesia - I Ketut Ngastawa; I Gusti Bagus Suryawan (Warmadewa Press, 2026)
State Administrative Law (HAN) reform is a strategic agenda in realizing the principles of the state of law and good governance. Although Indonesia is constitutionally a state of law, government administration practices still often deviate from the principles of legality, accountability, and legal certainty. This study analyzes the urgency of HAN reform by highlighting the problems of regulatory fragmentation, abuse of discretion, weak supervision, and low compliance with PTUN decisions. With a normative juridical approach, it is found that HAN reform is not enough to be carried out normatively, but needs institutional restructuring, strengthening legal culture, and optimizing supervision. HAN reform needs to be directed at harmonizing regulations, limiting discretion, strengthening administrative courts, and enforcing the execution of PTUN decisions. This effort is the key to upholding the rule of law and building a professional, clean, and fair government system.